2015
DOI: 10.3171/2014.11.spine14368
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal balance of the cervical spine: an analysis of occipitocervical and spinopelvic interdependence, with C-7 slope as a marker of cervical and spinopelvic alignment

Abstract: OBJECT Sagittal malalignment of the cervical spine has been associated with worsened postsurgical outcomes. For better operative planning of fusion and alignment restoration, improved knowledge of ideal fusion angles and interdependences between upper and lower cervical spine alignment is needed. Because spinal and spinopelvic parameters might play a role in cervical sagittal alignment, their associations should be studied in depth. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
61
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 23 publications
7
61
2
Order By: Relevance
“…In particular, cervical alignment has been suggested as an important factor associated with neck pain. 9,15,20,23 We sought to assess whether LPSF allows for greater neck pain relief when compared with laminoplasty for multilevel CSM in cohorts of patients with similar postoperative cervical lordosis. This study compared perioperative and followup outcomes of patients with matched cervical sagittal alignment who had undergone either laminoplasty or LPSF.…”
mentioning
confidence: 99%
“…In particular, cervical alignment has been suggested as an important factor associated with neck pain. 9,15,20,23 We sought to assess whether LPSF allows for greater neck pain relief when compared with laminoplasty for multilevel CSM in cohorts of patients with similar postoperative cervical lordosis. This study compared perioperative and followup outcomes of patients with matched cervical sagittal alignment who had undergone either laminoplasty or LPSF.…”
mentioning
confidence: 99%
“…Given the proximity of C7 to T1, several studies have suggested the use of C7 slope as a potential substitute for T1 slope in the assessment of cervical sagittal balance. [17][18][19] The more cephalad anatomical location of C7 makes it less susceptible to being obscured by the shoulders or thoracic trunk on lateral radiographs when patients are positioned in the standardized upright manner for radiographs. In this study, the endplates of C7 were indeed more easily visualized than the superior endplate of T1.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 To address these limitations, several authors have suggested using C7 slope as a proxy for T1 slope when the T1 superior endplate cannot be adequately visualized on radiographs. [15][16][17][18][19] The purpose of this study was 2-fold. First, we aimed to assess the correlation between C7 slope and T1 slope on upright radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Both C2-7 SVA and Cobb angle have been previously shown to correlate with radiographic failure and worse HRQOL; however, the C2-3 disc angle is a radiographic measure that has been minimally investigated to this point. 1,30,32,33,37,42,44 A study by Katsumi et al investigated the incidence of postoperative deformity leading to instability after decompression via laminectomy was performed in the cervical spine. 23 The authors demonstrated the presence of cervical instability at the C2-3 disc space after C2 laminectomy and that the C2-3 disc angle increased from 5.5° to 14.5°.…”
Section: Discussionmentioning
confidence: 99%